2019
DOI: 10.1111/nyas.14210
|View full text |Cite
|
Sign up to set email alerts
|

The role of ADGRE5/CD97 in human retinal pigment epithelial cell growth and survival

Abstract: Cell surface molecules of retinal pigment epithelial (RPE) cells participate in the pathogenesis of retinal diseases. In an attempt to identify cell surface proteins that play a role in RPE cell–cell interactions, we have considered studying the expression, regulation, and signaling of ADGRE5/CD97, an adhesion G protein–coupled receptor family member, based on its known adhesive function in other cell types such as leukocytes. We showed that RPE cells express three isoforms of CD97 and identified inflammation‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…27 Another study in human retinal pigment epithelium found that overexpression of CD97 activates MAPK signaling, as measured by increased serum response element (SRE)-driven luciferase expression in a luciferase-reporter system. 78 Interestingly, we did not observe this finding using an SRE-driven luciferase assay in our PDGCs, nor did we detect any other G protein-coupling of CD97 in GBM cells using other luciferase-driven reporter systems ( Supp. Fig.…”
Section: Discussionmentioning
confidence: 62%
“…27 Another study in human retinal pigment epithelium found that overexpression of CD97 activates MAPK signaling, as measured by increased serum response element (SRE)-driven luciferase expression in a luciferase-reporter system. 78 Interestingly, we did not observe this finding using an SRE-driven luciferase assay in our PDGCs, nor did we detect any other G protein-coupling of CD97 in GBM cells using other luciferase-driven reporter systems ( Supp. Fig.…”
Section: Discussionmentioning
confidence: 62%
“… 27 Another study in human retinal pigment epithelium found that overexpression of CD97 activates MAPK signaling, as measured by increased serum response element (SRE)-driven luciferase expression in a luciferase reporter system. 79 Interestingly, we did not observe this finding using an SRE-driven luciferase assay in our PDGCs, nor did we detect any other G protein coupling of CD97 in GBM cells using other luciferase-driven reporter systems ( Figure S4B ). We previously found that CD97 activated both MAPK and AKT signaling in leukemic stem cells.…”
Section: Discussionmentioning
confidence: 63%
“…ADGRE5 (CD97) has been considered as the most promising target of adhesion G protein‐coupled receptors in glioblastoma 44 . ADGRE5 in retinal pigment epithelial cells also controls leukocyte activation and trafficking in uveal retinal inflammation 45 . CD55, a complement regulatory protein, binds to multiple ligands that are constitutively expressed on monocytes or granulocytes and is rapidly upregulated during activation of T cells 46 .…”
Section: Discussionmentioning
confidence: 99%
“… 44 ADGRE5 in retinal pigment epithelial cells also controls leukocyte activation and trafficking in uveal retinal inflammation. 45 CD55, a complement regulatory protein, binds to multiple ligands that are constitutively expressed on monocytes or granulocytes and is rapidly upregulated during activation of T cells. 46 It has been shown that CD55 regulates both innate and adaptive immune responses and mediates T‐cell co‐stimulation when binding to CD97.…”
Section: Discussionmentioning
confidence: 99%